Q. 33.9( 433 Votes )

Obtain all other

Answer :

p(x) = 3x+ 6x- 2x- 10x - 5

Since the two zeroes are   .

is a factor of  3x+ 6x- 2x- 10x - 5.

Therefore, we divide the given polynomial by  .


We know,
Dividend = (Divisor × quotient) + remainder

3 x+ 6 x- 2x- 10 x - 5 =

3 x+ 6 x- 2 x- 10 x - 5 =
As (a+b)2 = a2 + b2 + 2ab

So, x2 + 2x + 1 = (x+1)2

3 x+ 6 x- 2 x- 10 x - 5 = 3 () (x + 1)2

Therefore, its zero is given by x + 1 = 0.
⇒ x = −1,-1

Hence, the zeroes of the given polynomial are  and - 1 , -1.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

When a polynomialRS Aggarwal - Mathematics

Find all the zeroRD Sharma - Mathematics